Verbal memory dysfunction is associated with alterations in brain transcriptome in dominant temporal lobe epilepsy - Busch, Robyn M.; Yehia, Lamis; Bazeley, Peter; Seyfi, Marilyn; Blümcke, Ingmar; Hermann, Bruce P.; Najm, Imad M.; Eng, Charis (Epilepsia, 2020)
Objective: Memory dysfunction is prevalent in many neurological disorders and can have a significant negative impact on quality of life. The genetic contributions to memory impairment in epilepsy, particularly temporal lobe epilepsy (TLE), remain poorly understood. Here, we compare the brain transcriptome between TLE patients with and without verbal memory impairments to identify genes and signaling networks important for episodic memory. Methods: Brain tissues were resected from 23 adults who underwent dominant temporal lobectomy for treatment of pharmacoresistant epilepsy. To control for potential effects of APOE on memory, only those homozygous for the APOE ε3 allele were included. A battery of memory tests was performed, and patients were stratified into two groups based on preoperative memory performance. The groups were well matched on demographic and disease-related variables. Total RNA-Seq and small RNA-Seq were performed on RNA extracted from the brain tissues. Pathway and integrative analyses were subsequently performed. Results: We identified 1092 differentially expressed transcripts (DETs), with the majority (71%) being underexpressed in brain tissues from patients with impaired memory compared to those from patients with intact memory. Enrichment analysis revealed overrepresentation of genes in pathways pertaining to brain-related neurological dysfunction, including a subset associated with neurodegenerative diseases, memory, and cognition (APP, MAPT, PINK1). Despite including patients with identical APOE genotypes, we identify APOE as a differentially expressed gene associated with memory status. Small RNA-Seq identified four differentially expressed microRNAs (miRNAs) that were predicted to target a subset (22%) of all DETs. Integrative analysis showed that these miRNA-predicted DET targets impact brain-related pathways and biological processes also pertinent to memory and cognition. Significance: TLE-associated memory status may be influenced by differences in gene expression profiles within the temporal lobe. Upstream processes influencing differential expression signatures, such as miRNAs, could serve as biomarkers and potential treatment targets for memory impairment in TLE.
CRIS-Team Scopus Importer:2020-09-25
Keywords: epilepsy surgery; memory; RNA-Seq; temporal lobe epilepsy; transcriptome